Keanekaragaman semut dan pola keberadaannya pada daerah urban di Palu, Sulawesi Tengah - Hasriyanty, Hasriyanty; Rizali, Akhmad; Buchori, Damayanti (Jurnal Entomologi Indonesia, 2015)
Land-use change, mainly from natural forest to agricultural or settlement area, beside have negative impact on biodiversity also cause a new problem such as the presence of pests. In urban area, the most intrusive and common pest is ant. The objective of this research was to study the occurrence pattern of ants in urban habitat. The research was conducted in several urban habitat in of Palu, Central Sulawesi include of settlement, garden, city park, shrub, agricultural area and forest margin. Ants were observed with bait trap using tuna and sugar. In total, we found 38 ant species from all gradients of urban habitat in Palu. Ant diversity were significantly correlated with habitat condition. Species richness and composition of ants tend to increase with decreasing degree of human disturbance (from settlement to forest margin). The most dominant ant that always found in all urban habitat are Anoplolepis gracilipes, Solenopsis geminata and Paratrechina longicornis. Those species are wellknown as tramp species that co-exist with human and have negative impact to local ant species. Urbanization and anthropological disturbance facilitate the occurrence of tramp ant species in Palu urban habitat.